2012
DOI: 10.1242/dev.073858
|View full text |Cite
|
Sign up to set email alerts
|

Deficient Notch signaling associated with neurogenicpecanexis compensated for by the unfolded protein response inDrosophila

Abstract: SUMMARYThe Notch (N) signaling machinery is evolutionarily conserved and regulates a broad spectrum of cell-specification events, through local cell-cell communication. pecanex (pcx) encodes a multi-pass transmembrane protein of unknown function, widely found from Drosophila to humans. The zygotic and maternal loss of pcx in Drosophila causes a neurogenic phenotype (hyperplasia of the embryonic nervous system), suggesting that pcx might be involved in N signaling. Here, we established that Pcx is a component o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(36 citation statements)
references
References 89 publications
(84 reference statements)
2
34
0
Order By: Relevance
“…Embryos were hybridized in situ as described previously (Takashima & Murakami, ). RNA probes of single‐minded ( sim ) were prepared as previously described (Yamakawa et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…Embryos were hybridized in situ as described previously (Takashima & Murakami, ). RNA probes of single‐minded ( sim ) were prepared as previously described (Yamakawa et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…We identified the ER (Boca and Pdi), Golgi (GM130), early endosomes (Hrs), late endosomes (Rab7), recycling endosomes (Rab11), and lysosomes (Lamp) by immunostaining (25,36,51,52,54). In wingdisc epithelial cells, the ER was detected either as an indistinct and shapeless structure (Fig.…”
Section: Somatic Mosaic Clones Homozygous For O-fut1mentioning
confidence: 99%
“…This IAP is integrated in the 5′-LTR-3-′LTR orientation in intron 19 of Pcnxl2 , the gene that encodes pecanex-like 2. Pcnxl2 is one of three mammalian paralogs of Drosophila melanogaster pecanex, a neurogenic gene about which little is known, but was recently suggested to be part of the notch signaling pathway in the endoplasmic reticulum [24], [25]. In adult mouse brain, Pcnxl2 is expressed highest in the hippocampal pyramidal cell layer, it is also expressed prominently in the area of cerebral cortex corresponding to layer V, and sparsely in the reticular thalamic nucleus (Allen Brain Atlas: see http://mouse.brain-map.org/experiment/show/70239051).…”
Section: Resultsmentioning
confidence: 99%
“…But no known primary or predicted secondary structures have been identified that would predict further function. D. melanogaster pecanex ( pcnx ) localizes to the endoplasmic reticulum (ER) and functional genetic studies utilizing the protein unfolded response as a readout, suggest that it shows maternal inheritance and has a role in notch signaling [25]. From conservation among pecanex family members we might expect that Pcnxl2 is also expressed in the ER.…”
Section: Discussionmentioning
confidence: 99%